Liquid air energy storage coupled with liquefied natural gas cold energy: Focus on efficiency, energy capacity, and flexibility. (1st February 2021) - Park, Jinwoo; Cho, Seungsik; Qi, Meng; Noh, Wonjun; Lee, Inkyu; Moon, Il
Abstract: A novel power-management-system design coupling liquid air energy storage (LAES) with liquefied natural gas (LNG) regasification is proposed that combines flexibility in responding to power demand, presented high energy efficiency and capacity. The proposed liquefied natural gas-thermal energy storage-liquid air energy storage (LNG-TES-LAES) process uses LNG cold energy via two different mechanisms. During on-peak times, when the proposed process requires no power consumption to meet the relatively higher electricity demand, LNG cold energy is recovered and stored via liquid propane. During off-peak times, the proposed process uses both cold energy from LNG and liquid propane, effectively doubling the cold energy available and enhancing the process flexibility. The liquid propane cold energy is used for air compression to reduce the power input requirement, while LNG cold energy is used mainly to liquefy air. These unique features afforded an electrical round-trip efficiency of 187.4% and an exergy efficiency of 75.1%, which are the highest among recently reported values. The energy capacity for the regasification of 1 MTPA LNG was 12.14 MW, which is adequate for bulk power management systems. By adopting flexibility, LNG cold energy has been distributed efficiently, and where LNG could be continuously regasified in the energy storage/release processes. Highlights: The proposed energy storage mechanism operates via multiple time-based modes. LNG cold energy was effectively used for air liquefaction and air compression. Electrical round-trip efficiency reached 187.4%, which is the highest recent value. Exergy efficiency reached 75.1%, and the process is economically feasible. The proposed process enabled flexible operations depending on energy demand.